Epiphytic mosses in mountain forests of Sochi region of the Black Sea coast (Russia) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Epiphytic moss component of different forest communities of Sochi region of the Black Sea coast (Russia) is characterized. Information about the distribution and frequency of 76 moss species, species richness and composition of moss complexes on the plots is analyzed.
Keywords: epiphytic mosses, forest communities, Sochi region, frequency, species richness.